From communism to capitalism nation and state in Romanian cultural production - Andreescu, Florentina C.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
This book offers an interdisciplinary mode of analyzing transitions from communism and planned economy to democracy and capitalism focusing on how the various social and political transformations are reflected within one hundred Romanian films produced during communism, transition, and post-transition.
Keywords: Science; Science; Science, general